Analisis Kualitas Pelayanan di Bagian Penerimaan Siswa Baru Menggunakan Metode Service Quality Pada SMK Wiyata Satya - Hamonangan, Samuel (Pusat Riset dan Inovasi Nasional, 2024)
Registration as a new student, both in public and private schools, is the first stage in the admission process. Every year, schools, including SMK Wiyata Satya, organize new student admissions (PSB) for prospective students who plan to register, especially for junior high, high school, or state vocational levels. PSB is an initial stage that is carried out every year to select prospective students based on their academic achievement, with the aim that they can continue their education to a higher level. In this study, we will discuss about service to prospective students today by applying the SERVQUAL (Service Quality) Method. In the application of the SERVQUAL Method, factors that can affect the quality of service in New Student Admissions (PSB) will be identified, by determining the attributes that play a role in influencing the level of customer satisfaction. . The Service Quality method is used to identify attributes that need to be improved in service quality, by detailing the gap between the service received and customer expectations. The purpose of implementing Service Quality is to meet customer needs. The concept of service quality and its environment. New Student Admission (PSB) is the first step that occurs every year for the selection of prospective students based on academic scores in order to continue their education at a higher level.